2011
DOI: 10.1096/fj.11-190249
|View full text |Cite
|
Sign up to set email alerts
|

Tapasin dependence of major histocompatibility complex class I molecules correlates with their conformational flexibility

Abstract: Major histocompatibility complex (MHC) class I molecules present cell internally derived peptides at the plasma membrane for surveillance by cytotoxic T lymphocytes. The surface expression of most class I molecules at least partially depends on the endoplasmic reticulum protein, tapasin, which helps them to bind peptides of the right length and sequence. To determine what makes a class I molecule dependent on support by tapasin, we have conducted in silico molecular dynamics (MD) studies and laboratory experim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
69
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 63 publications
(79 citation statements)
references
References 42 publications
10
69
0
Order By: Relevance
“…The simplest explanation for this effect is that, in the presence of the dipeptides, the structure of class I is more conducive to the binding of full-length peptide. Recently, the α 1 /α 2 domain of class I molecules that lack high-affinity peptide was shown to be significantly structurally disordered (24)(25)(26), and we propose that the dipeptides bind into the F pocket region to alleviate this molecular disorder. Because of their low affinity to class I (in the lower millimolar range; Fig.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…The simplest explanation for this effect is that, in the presence of the dipeptides, the structure of class I is more conducive to the binding of full-length peptide. Recently, the α 1 /α 2 domain of class I molecules that lack high-affinity peptide was shown to be significantly structurally disordered (24)(25)(26), and we propose that the dipeptides bind into the F pocket region to alleviate this molecular disorder. Because of their low affinity to class I (in the lower millimolar range; Fig.…”
Section: Discussionmentioning
confidence: 90%
“…S3 B and C), GL and the other dipeptides would then be expected to exchange rapidly in and out of the binding groove, allowing high-affinity peptide to bind to a temporarily stabilized empty state. Interestingly, we have previously postulated that tapasin fulfils a similar role in vivo by supporting a stable open state that binds peptides more easily than the disordered empty state of a class I molecule (25).…”
Section: Discussionmentioning
confidence: 99%
“…Evaluation of association and dissociation parameters of a battery of peptides, containing targeted departures from the model, revealed that peptide acquisition by H-2K b takes place in two distinct phases. During the first phase, the peptide-binding groove of H-2K b accepts a wide range of candidates, including even amino acid side chains much larger than their optimal size, which implies significant flexibility in the anchor residue-accepting pockets (17,(19)(20)(21)(22). Following the initial association event, ill-suited peptides exhibit greater propensity for dissociation and are thus selected against.…”
Section: Discussionmentioning
confidence: 99%
“…Structural Flexibility in the Peptide-Binding Groove of H-2K b . The peptide-binding groove should be flexible to accommodate expanded anchors (17)(18)(19)(20)(21)(22) (Table S4). In all structures the peptides could be resolved and fit into the electron density (Fig.…”
Section: Association and Disassociation Kinetics Of 9-mer Peptide Varmentioning
confidence: 99%
“…Many class I allotypes require tapasin for any binding of high-affinity peptides and subsequent surface transport and are thus termed tapasin-dependent; others do not, or to a lesser degree. With regard to the tapasin dependence of the B27 subtypes, conflicting reports exist [22,[24][25][26][27][28], and generally, it is not well understood what makes a particular class I allotype tapasindependent or -independent [21].In this work, we have compared the conformational stabilities of the B*27:05 and B*27:09 subtypes through a combination of in silico, biochemical, and cellular approaches. We find that the disease-associated B*27:05 is much more conformationally disordered than B*27:09 in the empty and suboptimally loaded states, and that it requires tapasin, at least to a large extent, for its surface expression.…”
mentioning
confidence: 99%